2012
DOI: 10.2460/javma.240.8.991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of xylazine bolus versus medetomidine constant rate infusion on cardiopulmonary function and depth of anesthesia in horses anesthetized with isoflurane

Abstract: In isoflurane-anesthetized horses, premedication with medetomidine followed by administration of medetomidine as a constant rate infusion resulted in decreased heart rate, higher arterial blood pressure from 20 through 40 minutes after induction of anesthesia, and better preserved body temperature, compared with conventional treatment with xylazine. Greater depth of anesthesia and muscle relaxation were seen with MCRI treatment, despite the lower isoflurane concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…In the previous comparison study of 1.7% of isoflurane versus 1.4% of isoflurane with medetomidine CRI, administration of medetomidine as CRI preserved more brisk eye reflexes when horses were maintained at 20%-30% lower inhalant anesthetic concentration, although the horses were at a similar plane of anesthesia during both treatments [13,20]. Traditionally, the depth of anesthesia in horses has been evaluated on the basis of ocular signs, such as spontaneous palpebral reflex and nystagmus.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the previous comparison study of 1.7% of isoflurane versus 1.4% of isoflurane with medetomidine CRI, administration of medetomidine as CRI preserved more brisk eye reflexes when horses were maintained at 20%-30% lower inhalant anesthetic concentration, although the horses were at a similar plane of anesthesia during both treatments [13,20]. Traditionally, the depth of anesthesia in horses has been evaluated on the basis of ocular signs, such as spontaneous palpebral reflex and nystagmus.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that medetomidine CRI reduced the minimum alveolar concentration (MAC) of desflurane by 28% in experimental ponies [16]. Others reported that isoflurane anesthesia in combination with medetomidine CRI resulted in improved cardiopulmonary function, analgesia, and muscle relaxation [13,15]. However, sevoflurane sparing effect of medetomidine CRI under surgical procedure has not been investigated in clinical cases.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Creighton et al. ). Dexmedetomidine is an α 2 ‐agonist with a pharmacokinetic profile that suggests it is suitable for administration as a CRI (Bettschart‐Wolfensberger et al.…”
Section: Introductionmentioning
confidence: 97%
“…Although BIS was originally designed for human subjects, studies have demonstrated its usefulness in anesthetic procedures in other species [10][11][12][13][14][15] . To the author's knowledge, limited data characterizing BIS in bovines have been published.…”
Section: Introductionmentioning
confidence: 99%